Zdravstvena vzgoja in dojenje - Hoyer, Silvestra (Zdravstveno varstvo, 2005)
Introduction: The article discusses the issue of health education on breast-feeding. It presents the activities of informing and educating mothers on breast-feeding, and stresses the importance of developing positiveattitudes about this issue. Health education in breast-feeding provided at the primary, secondary and tertiary levels is presented together with some health education programmes on breast-feeding from the foreign literature. Discussion and conclusion: The author finds health education on breast-feeding at primary level insatisfactory, and calls for intensified promotion activities to be taken in the field. At the secondary level, health education on breast-feeding is well-established and is provided through antenatal parenthood classes and brochures on breast-feeding. At the tertiary level, BFH and community services play a very active role in these health programmes, while other partners are not involved enough. It is important thathealth education in breast-feeding is provided as an interactive activityat all three levels, and that it combines different forms and methods of work, specially designed for and adapted to mothers and their partners.
Keywords: dojenje; food; prehrana; zdravstvena vzgoja